STUDY OF ACUTE TOXICITY OF BIS (TRIBUTYLTIN) OXIDE (TBTO) ON THE FRESHWATER FISH, NEMACHEILUS BOTIA, FROM NANDUR MADHMESHWAR DAM AT MAHARASHTRA, INDIA - S. M. NIKAM; K. B. SHEJULE (The Bioscan, 2015)
Acute toxicity of Bis (tributyltin) oxide (TBTO) has been studied on freshwater fish Nemacheilus botia. Static bioassays were performed on fresh water fish, N. botia to evaluate the median lethal concentrations of Bis (tributyltin) oxide (TBTO) for 24, 48, 72 and 96 hrs. The LC50 values were 0.01852, 0.0153, 0.01311 and 0.01099 ppm after 24, 48, 72 and 96 hours respectively. The results show that the LC50 values decreases with increase in exposure period.